(1→3)-β-D-Glucan Does Not Induce Acute Inflammation After Nasal Deposition. Issue 1 (24th February 2005) - Beijer Beijer, L. L.; Rylander Rylander, R. R.
Abstract : To assess if (1→ 3)-β -D-glucan, a microbial cell wall agent normally present in pollen, has the ability to produce pollenlike response, sensitive persons received a nasal deposition of two doses of (1→ 3)-β -D-glucan. The percentage of eosinophils and amount of eotaxin were measured in nasal lavage 30 minutes and 24 hours after challenge. No effect could be demonstrated. The absence of an inflammatory response after (1→ 3)-β -D-glucan application confirms earlier findings in inhalation studies.